SYNTHSIS A HIGHLY SENSITIVE MOLECULARLY IMPRINTEND POLYMER AS AN ELECTROCHEMICAL SENSOR FOR THE DETERMINATION OF AMLODIPINE IN PHARMACEUTICAL SAMPLES : SYNTHSIS A HIGHLY SENSITIVE MOLECULARLY IMPRINTEND POLYMER AS AN ELECTROCHEMICAL SENSOR FOR THE DETERMINATION OF AMLODIPINE IN PHARMACEUTICAL SAMPLES (Iraqi Journal of Market Research and Consumer Protection, 2024)
This paper demonstrates the synthesizing and storage of molecularly- imprinted polymers (MIP) at room temperature using bulk polymerization of amlodipine (AD) is characterized by high sensitivity, low costs and high stability. The research used 0.99:6:20 mmol ratios of template, monomer, and cross-linking agents for the polymerization in order to ensure an appropriate adsorption capacity. A functional monomer tripolyphosphate with cross-linking ethylene glycol dimethyl acrylate was attained by creating MIP for amlodipine as AD-MIP that could be characterized using a UV-VIS spectrophotometer at 238 nm, Fourier-transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). Mass spectrometric (MS) detection may use tritolylephosphate to determine amlodipine levels in pharmaceutical preparations. The GC/MS methods developed in this study are accurate, sensitive, and precise and can be easily applied to (AMADAY/India, NORVASC/U.K.) tablets in pharmaceutical preparation the elution process was applied to the template (AD) from the AD-MIP developed cavities caused by using pyrogenic solutions of methanol, chloroform, and acetic acid (70:20:10, v/v). The maximum adsorption capacity of AD-MIP was 0.263 µmol/g, and the ratio of template to monomer was 1:1 in adherence to the Langmuir isotherm model. A solid-phase extraction (SPE) syringe packed with molecularly imprinted polymers (MIPs) was used to selectively separate and pre-concentrate AD. from aqueous solutions and estimations of Amlodipine.